Das Mönchtum in der Religionspolitik Kaiser Justinians I. Die Engel des Himmels und der Stellvertreter Gottes auf Erden - Hasse-Ungeheuer, Alexandra (Millennium-Studien / Millennium Studies, 2015)
With his religious politics and his self-representation as the vicar of God on Earth, Justinian I (527-565) had an enduring impact on Late Antiquity. What part did monks, believed to be heavenly angels, play in promoting this notion? This book offers the first exhaustive investigation of Justinian`s personal relations to monkhood and the role of monks in religious and legislative politics.